2007
DOI: 10.1093/rheumatology/kel330
|View full text |Cite
|
Sign up to set email alerts
|

The 'distal-dorsal difference': a thermographic parameter by which to differentiate between primary and secondary Raynaud's phenomenon

Abstract: Parameters derived from thermography (incorporating both a heat and cold challenge) aid in the prediction of SSc in patients with RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
4
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 12 publications
1
64
4
4
Order By: Relevance
“…Several studies have reported that thermographic examinations are useful for differentiating secondary RP, such as systemic sclerosis, from primary RP (9,(13)(14)(15)(16)(17). In our study, the RP patients with systemic sclerosis had a significantly lower recovery rate and DDD and a significantly higher temperature disparity than the other patients with RP.…”
Section: Discussionsupporting
confidence: 47%
“…Several studies have reported that thermographic examinations are useful for differentiating secondary RP, such as systemic sclerosis, from primary RP (9,(13)(14)(15)(16)(17). In our study, the RP patients with systemic sclerosis had a significantly lower recovery rate and DDD and a significantly higher temperature disparity than the other patients with RP.…”
Section: Discussionsupporting
confidence: 47%
“…It has been used to evaluate the severity of vasoconstriction (Clark et al, 1999;Pauling et al, 2011). DDD of 41 1C in any finger at room temperature is considered a specific indicator of vascular disease (Anderson et al, 2007). Calculating the maximum DDD across all digits and the number of fingers with DDD 41 1C appeared to provide a greater discriminatory capacity than any other analysis that had been adopted in previous studies investigating DDD (Pauling et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…DDD is the difference in temperature between a finger and the dorsum of the hand (Anderson et al, 2007). It has a positive value if the finger is colder than the dorsum, and a high DDD indicates severe cold hypersensitivity in the fingers.…”
Section: Ddd Assessmentmentioning
confidence: 99%
“…Дисфункция эндотелия -патологическое состояние, возникающее в результате нарушения регионального кровообращения и микроцир-куляции, приводящее к усиленным тромбообразованию и адгезии лейкоцитов. Наибольшее значение имеет продук-ция оксида азота, эндотелина-1, серотонина, тромбокса-на и ангиотензина, уровень которых у больных с СР повы-шается под воздействием холода [10]. Регуляция сосуди-стого тонуса также вплотную связана с нейропептидами (связанный с геном кальцитонина пептид, нейропептид Y) и агентами, взаимодействующими с α-адренорецеп-торами, что дополнительно усиливает вазоконстрикцию.…”
Section: общность патогенеза вср и химunclassified